2011
DOI: 10.3390/molecules16065104
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Aroma Compounds from Different Pineapple Parts

Abstract: Characteristic aroma volatile compounds from different parts of cayenne pineapple were analyzed by headspace-solid phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC/MS). The main volatile compounds were esters, terpenes, ketones and aldehydes. The number and content of aroma compounds detected in pulp were higher than those found in core. In pulp, the characteristic aroma compounds were ethyl 2-methylbutanoate, ethyl hexanoate, 2,5-dimethyl-4-hydroxy-3(2H)-furanone (DMHF), decanal, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 17 publications
(22 reference statements)
2
74
0
1
Order By: Relevance
“…(2007) reported that hydrocarbons and esters were the main compounds, which could be explained by differences in cultivars, growing conditions, and volatiles extraction methods. Such differences could also justify why methyl butanoate and methyl 2‐methylbutanoate were not found in ‘Smooth Cayenne’ pineapple, despite being the most abundant components in other studies (Wei et al. , 2011).…”
Section: Resultsmentioning
confidence: 91%
“…(2007) reported that hydrocarbons and esters were the main compounds, which could be explained by differences in cultivars, growing conditions, and volatiles extraction methods. Such differences could also justify why methyl butanoate and methyl 2‐methylbutanoate were not found in ‘Smooth Cayenne’ pineapple, despite being the most abundant components in other studies (Wei et al. , 2011).…”
Section: Resultsmentioning
confidence: 91%
“…and 1.08%, respectively), and γ-hexalactone (0.96% and 1.09%, respectively) (Table 3). Wei et al (2011) identified 44 volatile compounds when characterizing pineapple pulp and core by headspace-solid phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC/MS). Some of them are the same as those identified in the present study, in which pineapple residues were characterized: methyl hexanoate, ethyl hexanoate, methyl 3-(methylthio) propanoate, methyl octanoate, ethyl decanoate, α-terpineol, nonanal, and decanal.…”
Section: Resultsmentioning
confidence: 99%
“…In the Bromeliaceae family, volatile compounds were studied in the Ananas genus and mostly the fruit volatile compounds. In Ananas over 280 compounds were identified, the most abundant being esters, terpenes, ketones and aldehydes (Tokitomo, Steinhaus, Suttner, & Schieberle, 2005;Liu, Wei, Sum, & Zang, 2008;Wei et al, 2011). Aguilar-Rodríguez et al (2014) identified nine volatile compounds (three fatty acid derivatives and six terpenoids) in T. macropetala, and correlated their presence to bat-pollination during a study of floral and reproductive biology.…”
mentioning
confidence: 99%